Case series: clinical outcomes of the transthyretin valine-to-isoleucine mutation in a brother–sister pair. Issue 4 (22nd October 2018) - Liu, Jason Y; Sara, Afrida; Liu, Jar-Yee; Fan, Judith; Gupta, Pritha; Wang, Jessica
Abstract: Background: Approximately 4% of the African-American population possess a valine-to-isoleucine (V122I) substitution within the transthyretin protein that results in a tendency for a normally tetrameric protein to dissociate into misfolded, monomeric subunits. These misfolded proteins can then accumulate pathologically and cause an autosomal dominant amyloid cardiomyopathy. Homozygous patients are infrequently documented in case reports, and though there are larger studies among heterozygous patients, there is a lack of studies or reports comparing disease within a family. Case summary: In this case series, we discuss a 61-year-old African-American male who succumbed to heart failure secondary to cardiac amyloidosis while awaiting orthotopic heart transplantation. We compare his case with that of his sister, a 65-year-old African-American woman with a history of recurrent supraventricular tachycardia requiring radiofrequency ablation, and intermittent chest pain with chronically elevated troponin despite no evidence of coronary artery disease. The sister in question was found to be homozygous for the transthyretin (TTR) V122I mutation with evidence of infiltrative process on cardiac magnetic resonance imaging, while clinical testing verified a heterozygous genotype in the brother. Here, we compare the clinical course and imaging data for the aforementioned brother–sister pair in the context of the amyloidogenic transthyretin V122I gene variant. Discussion: Through this familial report, we aim to highlight the variations in expression both within this family and in comparison, to the population. We also hope to emphasize the importance of genetic testing of families at risk for this specific transthyretin variant within the African-American community especially as novel therapies begin to emerge.